2014
DOI: 10.1111/jpy.12218
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and haplotype distribution of Pachymeniopsis gargiuli sp. nov. and P. lanceolata (Halymeniales, Rhodophyta) in Korea, with notes on their non‐native distributions

Abstract: The red alga Pachymeniopsis lanceolata, formerly known as Grateloupia lanceolata, is a component of the native algal flora of northeast Asia and has been introduced to European and North American waters. It has been confused with a cryptic species collected from Korea and Italy. Our analyses of rbcL, cox3 and ITS from P. lanceolata and this cryptic species has revealed two distinct entities, forming a clade, which were clearly separated from its congeners and positioned with other Asian species. Here, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…MSK 2013-14 (KJ648553, KF475723) from Korea. All these sequences formed a monophyletic clade together, apart from the highly related G. lanceolata (which has been synonymised with Pachymeniopsis lanceolata (K. Okamura) Y. Yamada ex S. Kawabata (Kim et al, 2014) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…MSK 2013-14 (KJ648553, KF475723) from Korea. All these sequences formed a monophyletic clade together, apart from the highly related G. lanceolata (which has been synonymised with Pachymeniopsis lanceolata (K. Okamura) Y. Yamada ex S. Kawabata (Kim et al, 2014) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…5) clearly showed the correct identity since samples from this study showed 100% identity with sequences of P. gargiuli (KJ125446, KJ214447), a recently described species closely related to P . lanceolata as described by Kim et al (2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of seaweeds based on morphology is a classical method, so DNA-based molecular techniques have increasingly been used for taxonomical identification. These studies interested mainly on the use of DNA sequences to elucidate taxonomic and systematic issues (Kim et al 2014). Among these techniques DNAbarcoding where a short piece of DNA is used to distinguish between species.…”
Section: Introductionmentioning
confidence: 99%